Mapping Health Needs to Support Health System Management in Poland - Holecki, Tomasz; Romaniuk, Piotr; Woźniak-Holecka, Joanna; Szromek, Adam R.; Syrkiewicz-Świtała, Magdalena (Frontiers in Public Health, 2018)
In Poland, following the example of other EU countries, the first maps of health needs prepared by the Ministry of Health were presented in 2016. The maps constitute a foundation for rational decision-making in the management of health care resources, being potentially useful for all actors in health system. This refers in particular to the institutions responsible for distribution of funds and contracting health service, but also for decision-makers, who determine the scope of funds to be utilized in the health system, or the structure of benefits provided to patients. Service providers are also addressees of the maps, to give them a basis for planning future activities. The article presents a structured assessment of the current state of affairs, based on recent experience and sets out likely directions for the development of health needs in mapping in Poland in the future. We discuss the criticism addressed toward maps by representatives of various groups acting in health care. It includes the lack of recognition of some of the key health needs, or wrong emphases, where much more attention is paid to the recognition of current resources in the health system, instead of making prognoses regarding the future developments of health needs. Nonetheless, we find that this instrument is potentially of high usability, in case of elimination of the existing weaknesses.